1995
DOI: 10.1172/jci117833
|View full text |Cite
|
Sign up to set email alerts
|

Secondary alcohol metabolites mediate iron delocalization in cytosolic fractions of myocardial biopsies exposed to anticancer anthracyclines. Novel linkage between anthracycline metabolism and iron-induced cardiotoxicity.

Abstract: IntroductionThe cardiotoxicity of doxorubicin (DOX) and other quinone-containing antitumor anthracyclines has been tentatively attributed to the formation of drug semiquinones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
3
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 52 publications
3
80
3
1
Order By: Relevance
“…Daunorubicin, G. Sacco et al MEN 10755, alcohol metabolites, cardiotoxicityand especially 4-demethoxydaunorubicin (idarubicin), seem to be less cardiotoxic than DOX but the levels of their alcohol metabolites in plasma may be higher than those of DOXol (Danesi et al, 2002). In considering such inconsistency one should keep in mind that the expression and substrate specificity of anthracycline reductases may vary widely from blood cells to a given tissue or another, the yield of daunorubicinol or idarubicinol being higher or lower than that of DOXol depending on whether the parent anthracyclines are metabolized by specific families of carbonyl reductases or aldo/keto reductases, respectively (Forrest et al, 1991;Minotti et al, 1995). Moreover, circulating metabolites do not always exhibit good partitioning inside the heart, making it uncertain whether they actually contribute to inducing cardiotoxicity (Olson & Mushlin, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Daunorubicin, G. Sacco et al MEN 10755, alcohol metabolites, cardiotoxicityand especially 4-demethoxydaunorubicin (idarubicin), seem to be less cardiotoxic than DOX but the levels of their alcohol metabolites in plasma may be higher than those of DOXol (Danesi et al, 2002). In considering such inconsistency one should keep in mind that the expression and substrate specificity of anthracycline reductases may vary widely from blood cells to a given tissue or another, the yield of daunorubicinol or idarubicinol being higher or lower than that of DOXol depending on whether the parent anthracyclines are metabolized by specific families of carbonyl reductases or aldo/keto reductases, respectively (Forrest et al, 1991;Minotti et al, 1995). Moreover, circulating metabolites do not always exhibit good partitioning inside the heart, making it uncertain whether they actually contribute to inducing cardiotoxicity (Olson & Mushlin, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines act by inhibiting DNA and RNA synthesis, blocking topoisomerase II to prevent DNA and RNA transcription and replication, and creating iron-mediated free radicals that damage DNA [6]. The pathogenesis of Doxinduced cardiotoxicity and heart failure is complex and may involve various signaling mechanisms including selective inhibition of cardiac muscle gene expression [7], disturbance of myocardial adrenergic signaling [8], cellular toxicity from metabolites of DOX [9], induction of cardiac cell apoptosis [10], production of reactive nitrogen species [11] and a number of DOX-induced biochemical changes have been identified that can damage cardiac reactive oxygen species [12]. Free radical damage to cardiac myocytes is thought to be the primary mechanism for anthracycline-induced cardiomyopathy [13] and also by induction of immunogenic reactions with the presence of antigen presenting cells in the heart [14].…”
Section: Introductionmentioning
confidence: 99%
“…The process of a one-electron transfer is catalysed by a range of cellular oxidoreductases, mainly NADH dehydrogenase, NADPH cytochrome P450 reductase (CPR), xanthine oxidase (Mordente et al, 2001;Pawłowska et al, 2003) and nitric oxide synthase (Vasquez-Vivar et al, 1997;Garner et al, 1999). Subsequent nonenzymatic semiquinone radical reoxidation by molecular oxygen can form reactive oxygen species (O 2 metabolism of DOX could also lead to the deglycosylation of the drug catalysed by cellular oxidoreductases (mentioned above) via a one-electron transfer or to the formation of doxorubicinol in the presence of specific enzymes namely aldo -keto reductases and carbonyl reductases catalysing a two-electron reduction of the drug (Minotti et al, 1995). These metabolic pathways of DOX play an important role in the detoxication steps (Bernardini et al, 1991;Ferrazzi et al, 1991), although doxorubicinol can also contribute to the development of the dose-limiting cardiotoxicity (Olson et al, 1988;Forrest et al, 2000).…”
mentioning
confidence: 99%